Consumer perceptions of a perilous product: International tourism to South Africa - Mike Bendixen; Denis Cranson; Russell Abratt (South African Journal of Business Management, 1996)
Tourism can make a significant contribution to the development of South Africa by providing employment, contributing to foreign exchange earnings and by increasing economic activity. The aim of this study was to establish current perceptions, attitudes and orientations of foreign tourists towards post-apartheid South Africa as a tourist destination. A sample of 250 tourists were interviewed at London's Heathrow Airport. The results show that the South African tourism industry is faced with a multidimensional problem. It is a good example of a perilous or high risk product. However, with sound market segmentation and targeting, and proper planning, South Africa can have a vibrant and sustainable tourism industry. A unique way of segmenting tourist markets is presented. Specific recommendations are discussed in detail, which could aid all those involved in marketing a high risk product.
Keywords: 650